Walking the beat on the path to technology - developing computer savvy police - Armstrong, Helen; Russo, P. (Moscow Engineering Physics Institute (State University), Russia, 2005)
This paper focuses on a joint project to develop specialized training for law enforcement in the search and seizure of electronic evidence. The paper describes the training program developed jointly by law enforcement and academic staff and presented to law enforcement officers in the state of Western Australia, and reports informally on the success of the program.